Bronchiectasis-COPD Overlap Syndrome (BCOS) among the Nepalese Patients: Emerging disease from a developing country - Acharya, Achyut Bhakta; Bhattarai, Narendra; Mishra, Deebya Raj; Karki, Prahlad; Gupta, Mukesh Kumar; Lamsal, Madhab; Khanal, Basuda (Nepalese Respiratory Journal, 2023)
Background and objective: There is no clearly specified diagnostic criteria to identify BCOS in Nepalese context. So this first, observational cross-sectional study was conducted to determine the current situation, main clinical practices, and features of BCOS in Nepalese patients, exploring its clinical trajectory and severity. Methods: This is a hospital based descriptive cross-sectional study conducted, where patients presenting with respiratory symptoms complex were subsequently enrolled by purposive sampling. Descriptive Statistics was calculated using Absolute and Relative Frequencies for categorical variables and mean and standard deviation for numerical ones. P-value of <0.05 was considered significant. Results: Out of 236 patients of Respiratory Symptoms Complex, prevalence of BCOS was 22.03%. 57.7% were males with mean age of 67.8 years. Among BCOS cohorts, 92.3% were smokers and 73 % had significant exposure to indoor air pollution. 63.5% of the patients had past history of tuberculosis and cardio-metabolic co-morbidities were seen in 34.6% of the patients. The most frequent symptoms were cough and shortness of breath and the commonest sign was bilateral basal coarse crackles. Frequent exacerbations were present in 25% of the patients and PFT revealed obstructive pattern in 71% of the BCOS patients with a mean FACED score of 3.94±1.62. Conclusion: Among the patients presenting with Respiratory symptom complex in Nepal, BCOS is common and is more prevalent in elderly male, having a high co-morbidities, usually following a course of slowly progressive breathlessness, with higher incidence of exacerbation and poorer functional outcome.